The Role Of Social Media And Literacy In Early Awareness Of Health Diabetes Complications - Dzulfikar Fatih; Hasna Mufarraha; Ziyadi Nor Irfan (CV. AFDIFAL MAJU BERKAH, 2026)
Advances in digital technology have made social media one of the main channels for disseminating health information to the public. This study aims to examine the influence of social media and health literacy levels on increasing early awareness of complications in people with diabetes mellitus. Social media acts as an interactive platform that facilitates the dissemination of knowledge, education, and the exchange of experiences between individuals in managing diabetes. However, the successful use of social media is highly dependent on the health literacy of users. This study uses a quantitative approach with a survey method, where data is collected through a 5-point Likert scale questionnaire (1 = strongly disagree to 5 = strongly agree). The study population consists of students aged 18–20 years from the 2024 and 2025 cohorts, with a sample size of 77 respondents selected using purposive sampling. The research instrument covered three main variables, namely social media use, health literacy, and early awareness of diabetes complications. The data were analyzed using descriptive statistics and multiple linear regression analysis to determine the influence between variables. The results of the study indicate that wise use of social media and a high level of health literacy have a positive and significant effect on increasing early awareness of diabetes mellitus complications. Individuals with good literacy are better able to select valid information, understand the risks of complications such as retinopathy, nephropathy, and diabetic neuropathy, and independently implement preventive measures. The overall Cronbach's alpha coefficient (0.773) is greater than 0.60, so with a significance level or α = 5%, the questionnaire is reliable (consistent). Therefore, synergy between health workers, educational institutions, and policymakers is needed to maximize the role of social media as a reliable and effective means of health education